Cervical Hemangioma In Pregnancy - I Putu Bagus Mulyana Yoga; Anak Agung Gede Raka Budayasa (Ridwan Institute, 2022)
Hemangioma in the uterine cevix is a rare case, especially during pregnancy. Hemangioma is a benign tumor, but it can cause complication namely antepartum bleeding, preterm labour, and severe, life threatening complication such as disseminated intravascular coagulation (DIC). Histopathology examination is needed to diagnose hemangioma, and to differentiate this disease with other pathological condition. Conservative therapy was chosen as the main option rather than surgical therapy. The case report explain about 2 cases with cervical hemangioma in the uterine in 2 pregnant women. In the case 1 we presented a 27 years old primigravida, 29th weeks gestational age, with antepartum bleeding. A cervical biopsy was done and the histopathological examination reveal a capillary hemangioma within the uterine cervix. The patient was followed up with medications, and a caesarean section was planned to deliver the baby. In the case 2, a 30 years old multigravida with complained of postpartum bleeding. The clinical manifestation of cervical hemanioma in pregnancy was similar with other pathological condition, such as cervical cancer. A better understanding in pathogenesis and histopathological examination is important to differentiate hemangioma and other pathological condition in uterine cervix. Therapeutic modality was still debated, because of the limitation of literature about hemangioma cervix, especially in pregnant women